letter to the editor about a published article DOI: 10.2196/mhealth.8458 - Johan Goris (2017)
Unlabelled Health care providers are among the most trusted professionals, and they are rapidly adapting to AI integration in medicine. Authors Hou et al reviewed and synthesized qualitative studies of patient concerns regarding AI in health care. Themes included privacy, data security, and the "black box" complexity of AI decision-making; decreased trust in the physician-patient relationship and in the accountability of health systems; and equitable access, ethical regulation, and the displacement of human workers. Global and national health leaders can support health systems by establishing specific guidelines for informed consent about AI use in patient care. Similarly, health care leadership groups, in collaboration with AI developers, should establish checkpoints for physician review and specific loci for accountability prior to clinical use. Equitable access, ethical regulation, and the preservation of access to human providers, particularly when empathetic holistic care is paramount, will all impact the future of patient trust in physicians and health care systems. Centering our actions on the concerns of patients provides a road map to improve health care delivery, with AI at the service of patients and physicians.